Evaluación volumétrica cardíaca por angiotomografía y falla del ventrículo derecho en pacientes con embolia pulmonar aguda: revisión sistemática de la literatura (2019)
Introduction: Acute pulmonary embolism has a mortality rate that reaches up to 58%, with heart adaptation mechanisms to right ventricular strain as the main factor determining outcomes. The gold standard for diagnosis of right ventricular failure is echocardiography, but it has some limitations as it is operator dependent and the technical difficulties of acquiring adequate images of the right cardiac chambers. There have been performed some trials testing conventional tomography (CT) as a diagnostic tool for determining hemodynamic alterations derived from this pathology, however none of them has demonstrated an acceptable diagnostic performance. Along with the advent of new CT technologies having better acquisition hardware and post-processing software, it has been possible to measure the cardiac chamber volumes to make appropriate comparisons with those obtained through echocardiography. Objective: to perform a systematic review of the diagnostic validity of cardiac chamber volume determined on ECG-gated heart CT for the diagnosis of right ventricular failure. Materials and methods: it was performed a systematic review on the validity of cardiac volumetric measurements calculated through ECG-gated heart CT as a diagnostic tool compared with those obtained through echocardiography as it is the reference standard in diagnosis of right ventricular failure, finding a combined sensitivity of 0.89 % (0.76-0.95; CI 95) and a specificity of 87% (9.79-9.93%; CI 95). Conclusions: actual scientific evidence supports the use of heart chamber volume measurements obtained through ECG-gated heart CT as a diagnostic tool in determining right ventricular failure on patients having an acute pulmonary embolism, with a good diagnostic performance.